Productividad nutricional del pasto maralfalfa (pennisetum sp.) con abonamiento orgánico en el Ciey-Unap Km 17, Yurimaguas - Rodriguez de la Viuda Barrantes, Rodolfo (2024)
The study was carried out at CIEY, Km 17-UNAP, with the aim of evaluating the nutritional productivity of maralfalfa grass (Pennisetum sp.) with organic fertilizer; for which the following treatments were used: T0 without fertilizer; T1 cow manure 12 kg / 6 m2; T2 cow manure 18 kg / 6 m2; T3 chicken manure 12 kg / 6 m2 and T4 chicken manure 18 kg / 6 m2; the parameters evaluated were percentages of crude protein (CP), fiber and ash; a statistical design Completely Randomized Blocks (DBCA) was used with 5 treatments and 4 repetitions; the results were subjected to the Tukey test. The effect of organic fertilizers was evaluated at 45 and 60 days after the uniformization cut; regarding the % of crude protein, significant statistical differences were found, highlighting T4 with 8.65% of crude protein at 45 days; Similarly, at 60 days, significant statistical differences were also found, where T4 showed the highest protein values with 10.41%. Regarding the crude fiber (CF) content, significant statistical differences were found in the two cutting times; where T4 reported 33.42% CF at 45 days and the same T4 obtained 37.36% CF was higher at 60 days. Regarding the % of ash, there were significant statistical differences between the treatments in the Tukey test, T3 at 45 days obtained 9.21%; and at 60 days T4 reached 12.23%, showing significant differences with respect to T0. These results indicate that, using organic fertilizers (cow manure and chicken manure), the % of protein, fiber and ash of the grass are maintained in adequate proportions and guarantee adequate feeding of the cattle and increase their productivity in a sustainable and environmentally friendly way.